PENGARUH SUHU DAN TEKANAN INJEKSI TERHADAP CACAT SHORT SHOT PRODUK POLIKARBONAT PADA MESIN INJECTION MOLDING (STUDI KASUS DI PT. SEJONG MATRASINDO SEMARANG) - Langga, Ega Holian Meilia; Syabani, Muh Wahyu; Wulung, Raden Bagus Seno (Politeknik ATK Yogyakarta, 2017)
Nowadays, the application of the plastic covers a lot of aspects in the human activities, including on the leather products industry. The most common plastic producing processes used is injection molding. One of the plastics production primary problems in injection molding is short shots defect. The defect occurs because the melting plastic did not fulfill completely the mold cavity since the process parameters are not optimum. In This study analyzes the effect of the injection pressure and temperature on the short shots defect that occurs at polycarbonates production. The injection pressures and temperatures are varied, but keep the other process parameters at certain value. The result shows that at the constant temperature of 260oC, higher injection pressure would give lower defects for pressure range from 3 to 24 MPa. At 6 MPa the defects reach zero. When using various temperatures from 195 to 280oC at constant pressure of 3 MPa, the results shows that higher temperature would gives lower short shot defect.